Clinical evidence construction of East Asian herbal medicine for inflammatory pain in rheumatoid arthritis based on integrative data mining approach. (November 2022) - Jo, Hee-Geun; Seo, Jihye; Lee, Donghun
Abstract: Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease that leads to a significant social burden. East Asian herbal medicine (EAHM) has long been used to treat RA. Therefore, a systematic study of how EAHM treatments can be developed into new drugs using specific materials is needed. Methods: Eleven databases containing literature in English, Korean, Chinese, and Japanese were searched for randomized controlled trials comparing EAHM with conventional medicine (CM). A meta-analysis was performed on the variable data to assess their effects on inflammatory pain. Subsequently, we searched for core materials and combinations of core material-based data mining methods. Results: A total of 186 trials involving 19, 716 patients with RA met the inclusion criteria. According to the meta-analysis, EAHM had a significantly superior effect on continuous pain intensity, tender joint count, and response rate. Patients treated with EAHM had a significantly reduced incidence of adverse events compared with those treated with CM. Based on additional analysis of the EAHM formula data included in this meta-analysis, 21 core materials and five core herbal combinations were identified. Conclusion: EAHM remedies for RA have the adequate potential for use as candidate materials for treating inflammatory pain in RA. The candidate core herbs evaluated in this study act on multiple pathways and are expected to provide pain relief, sustained inflammation suppression, immune regulation, and prevention of joint destruction. It seems worthwhile to conduct follow-up research on drug development using the core materials derived from this review. Graphical Abstract: ga1 Highlights: East Asian herbal medicine (EAHM) can elicit an inhibitory effect equivalent to conventional medicine on the inflammatory pain in rheumatoid arthritis. EAHM is superior to conventional medicine in terms of safety in patients with rheumatoid arthritis. In this study, twenty-one individual core herb materials and five core herb combinations derived through data mining were considered worthy of further research as new pharmaceutical drug candidates for inflammatory pain in rheumatoid arthritis. A combination of systematic review and data mining techniques can potentially help identify EAHM-based candidate drug.